Next-Generation Sequencing of Antibody Display Repertoires - Rouet, Romain; Jackson, Katherine J. L.; Langley, David B.; Christ, Daniel (Frontiers in Immunology, 2018)
In vitro selection technology has transformed the development of therapeutic monoclonal antibodies. Using methods such as phage, ribosome, and yeast display, high affinity binders can be selected from diverse repertoires. Here, we review strategies for the next-generation sequencing (NGS) of phage- and other antibody-display libraries, as well as NGS platforms and analysis tools. Moreover, we discuss recent examples relating to the use of NGS to assess library diversity, clonal enrichment, and affinity maturation.